Review on the Students’ Speaking Skill (A Case Study of the 6th Semester Students Attending Microteaching Class) - Sri Wahyuni; Siti Lestari (Universitas PGRI Semarang, 2021)
Teaching practice is one of the main activities for the 6th semester students who are attending Microteaching class. Students have the opportunity to have teaching practice with their peers. They have to learn the basic skill in teaching and also learn how to speak in front of the class by applying the language classroom expression. To be a good teacher, they have to speak well in using the language classroom expression and when they speak well it will affect their teaching activity in class. Since speaking skill is very important in teaching, it is part of our interest to find out how well the students’ speaking skill in microteaching class. This paper will share the result of our observation and analysis on the students’ speaking skill by analyzing their competence in: 1) pronunciation 2) grammar, and 3) vocabulary. Twenty (20) students, as the sample, will be video recorded and then the records were analyzed based on those three components. It shows that intensive practice is still needed concerning with those three components as mentioned before. The result of this observation and analysis will be very important for the lecturers to consider when they teach microteaching class.